Synthesis, reactivity, and structure of strictly homologous 18 and 19 valence electron iron nitrosyl complexes. - Sellmann, Dieter; Heinemann, Frank Wilhelm; Heß, Bernd Artur; et al. (Chemistry - A European Journal, 2001)
The 18 and 19 valence electron (VE) nitrosyl complexes [Fe(NO)('pyS4')]BF4 ([1]BF4) and [Fe(NO)('pyS4')] (2) have been synthesized from [Fe('pyS4')]x ('pyS4'(2-) = 2,6-bis(2-mercaptophenylthiomethyl)pyridine(2-)) and either NOBF4 or NO gas. Complex [1]BF4 was also obtained from [Fe(CO)('pyS4')] and NOBF4. The cation [1]+ is reversibly reduced to give 2. Oxidation of 2 by [Cp2Fe]PF6 afforded [Fe(NO)('pyS4')]PF6 ([1]PF6). The molecular structures of [1]PF6 and 2 were determined by X-ray crystallography. They demonstrate that addition of one electron to [1]+ causes a significant elongation of the Fe-donor atom bonds and a bending of the FeNO angle. Density functional calculations show that the unpaired electron in 2 occupies an orbital, which is antibonding with respect to all Fe-ligand interactions. As expected from qualitative Molecular Orbital (MO) theory, it has a large contribution from a pi* type NO orbital. The nu(NO) frequency decreases from 1893 cm(-1) in [1]BF4 to 1648 cm(-1) in 2 (in KBr). The antibonding character of the unpaired electron explains the ready reaction of 2 with excess NO to give [Fe(NO)2('pyS4')] (3), the facile NO/CO exchange of 2 to afford [Fe(CO)('pyS4')], and the easy oxidation of 2 to [1]+.
UnivIS-Import:2017-03-24:Pub.2001.forsch.sonder.sfb583.synthe
Keywords: Density functional calculations; Iron; Nitrosyl complexes; S ligands; Structure elucidation